PENGARUH UKURAN PERUSAHAAN, LEVERAGE, UKURAN DEWAN KOMISARIS DAN PROFITABILTAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG GO PUBLIC TAHUN 2016-2018 DI BURSA EFEK INDONESIA) - Sugeng, Andry (Universitas Sam Ratulangi, 2020)
This study aims to analyzie and obtain empirical evidence about the effect company size, leverage, board of commisioners and profitability on the corporate social responsibility disclosure to coal mining companies in Indonesia. The independent variables of this study are company size, leverage, board of commisioners, and profitability while the dependent variable of this study is the disclosure of corporate social responsibility. The study conducts multiple regression analysis by using mining companies which listed in the Indonesia Stock Exchange (BEI) over period between 2016 to 2018 with a total of 44 companies. This study collects the data by purposive sampling method that makes the total sample is 17 companies with 51 data of financial statements companies as research observations. This study finds that: (1) company size not significant effect to corporate social responsibility disclosure;(2) leverage not significant effect to corporate social responsibility disclosure;(3) board of commisioners not significant effect to corporate social responsibility disclosure; and (4) profitability significantly effect to corporate social responsibility disclosure.